COSO-based internal control: efforts towards good university governance - Junusi, Rahman El (Universitas Islam Negeri (UIN) Walisongo Semarang, 2020)
Purpose - The purposes of this study are to determine the implementation of internal control, to determine the application of good university governance, and to determine the effect of internal control on good university governance.Method - The research design is a survey with a quantitative approach. The object of research is UIN Walisongo that has carried out an institutional transformation. The population in this study is all structural officials at UIN Walisongo with 184 people in total. From the distribution of questionnaires, 106 questionnaires were obtained. The analysis technique used is descriptive analysis and Structural Equation Modeling (SEM) analysis with the AMOS program.Result - The results showed that the application of internal control was carried out in the good category, the application of university governance was in the very good category, and internal control had a significant effect on good university governance.Implication - The result of the study provide further confirmation of internal control with good university governance. This study, carried out in one educational institutions, therefore more educational institutions are needed to be examined so that the result can be generalized.Originality - The research focuses on educational institutions that specialize in teaching, research and community service. Especially the dimensions of risk analysis are generally discussed in profit organizations.